NUTRITIONAL STATUS OF PREGNANT WOMEN IN RELATION TO THE PREVALENCE OF INFANT LOW BIRTH WEIGHT (LBW) (Case Study in Sugihwaras, Bojonegoro during 2017) - Fitriana Ikhtiarinawati Fajrin (Journal of Research and Technology, 2018)
This study aims to analyse the relationship of nutritional status of pregnant women with the prevalence of LBW. A quantitative study with the descriptive analytic design was conducted using cross-sectional approach in primary health care (Puskesmas) Sugihwaras, Bojonegoro.The subject of this study is all babies with Low Birth Weight (LBW) at Puskesmas Sugihwaras Bojonegoro. Hence, the sampling technique was total sampling. Data was collected using secondary data instrument such as medical record and mother-child healthreport (KIA) from Puskesmas Sugihwaras. Nutritional status of pregnant women was assessed based on measurement of Mid-upper Arm Circumference. The spearman rank correlation test showed that there is a significant correlation (p-value <0,05)between nutritional status of pregnant mother with the prevalence of LBW in Puskesmas of Sugihwaras, Bojonegoro.